Perspectives of Socio-Scientific Issues in Educational Research: A Bibliometric Analysis - Narayanan, Binesh; Kumar, Amruth G.; Gunasekaran, Dinesh; Vengayil, Rajasree; Maduvegadde, Krithika; Alampady, Nirmala (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
The intricate nature of socio-scientific issues has gained traction among researchers in recent decades. This study explores educational research focused on socio-scientific issues over the last 21 years (2002-2023) using the bibliometric method. The analysis of 350 Scopus-indexed articles was conducted, examining publication trends, influential contributors, and research trajectories through citation, co-occurrence, and co-citation analyses. Co-citation analysis reveals a complex intellectual structure within the field, with a dominant cluster of influential authors and several smaller, specialized research communities emerging. Analysis revealed that the major themes discussed by the examined articles include the nature of science, climate-change decision-making, and education for sustainability, which are crucial in addressing contemporary challenges in education and society. This study highlights the significance of fostering interdisciplinary cooperation and integration of technological aspects into future research. It also identifies the necessity of addressing gaps in research resources, improving knowledge accessibility, and strengthening international collaborations for the field's advancement.